2018
DOI: 10.1177/2333794x18788174
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Simple Anthropometric Measurement to Identify Low-Birth-Weight Infants in Enugu, Nigeria

Abstract: Background. This prospective study was conducted to identify a suitable alternative to birth weight and establish its cutoff point to facilitate the identification of low-birth-weight (LBW) infants in Enugu, Southeast Nigeria. Methods. The study involved newborn babies within the first 48 hours of life. Five anthropometric measurements (head, chest, mid-arm and calf circumferences, as well as abdominal girth) were taken using a tape measure while supine length was measured with an aluminum infantometer. Birth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…Berat lahir yang tidak ditimbang maupun bayi yang tidak memiliki catatan penimbangan juga menjadi masalah pada beberapa negara berkembang lain (Hadush et al, 2017;Marchant et al, 2010;Nabiwemba et al, 2013;Otupiri et al, 2014;Sreeramareddy et al, 2008). Oleh karena itu berbagai penelitian dilakukan untuk menemukan ukuran pengganti berat lahir untuk dapat mendeteksi kasus BBLR diantaranya panjang telapak kaki (Marchant et al, 2010;Nabiwemba et al, 2013), lingkar dada (Chukwudi et al, 2018;Hadush et al, 2017;Mullany et al, 2007;Otupiri et al, 2014;Sreeramareddy et al, 2008), lingkar kepala (Hadush et al, 2017;Taksande et al, 2007), lingkar lengan atas (Goto, 2011;Neeluri & Pamarthi, 2018;Otupiri et al, 2014;Vaik P et al, 2017;Verma et al, 2014), dan lingkar betis (Otupiri et al, 2014;Sheikh et al, 2017;Suneetha & Kavitha, 2016;Sunil Kumar, Sudarshan, & Vatsala, 2013) Pendeteksian BBLR secara cepat dan penanganan yang tepat merupakan hal yang penting terutama dalam kelangsungan hidup bayi (Administrative Committee on Coordination/ Subcommittee on Nutrition, 2000; Pojda & Kelley, 2000), namun sulit dilakukan jika persalinan terjadi di rumah dan tidak ditolong oleh non tenaga kesehatan yang disebabkan karena ketidaktersediaan alat penimbangan atau tidak adanya tenaga pengukur yang terlatih (Kusharisupeni et al, 2013;Neeluri & Pamarthi, 2018;Suneetha & Kavitha, 2016). Oleh karenanya diperlukan alternatif metode pendeteksian BBLR yang cepat, akurat dan mudah dilakukan.…”
Section: Pendahuluanunclassified
“…Berat lahir yang tidak ditimbang maupun bayi yang tidak memiliki catatan penimbangan juga menjadi masalah pada beberapa negara berkembang lain (Hadush et al, 2017;Marchant et al, 2010;Nabiwemba et al, 2013;Otupiri et al, 2014;Sreeramareddy et al, 2008). Oleh karena itu berbagai penelitian dilakukan untuk menemukan ukuran pengganti berat lahir untuk dapat mendeteksi kasus BBLR diantaranya panjang telapak kaki (Marchant et al, 2010;Nabiwemba et al, 2013), lingkar dada (Chukwudi et al, 2018;Hadush et al, 2017;Mullany et al, 2007;Otupiri et al, 2014;Sreeramareddy et al, 2008), lingkar kepala (Hadush et al, 2017;Taksande et al, 2007), lingkar lengan atas (Goto, 2011;Neeluri & Pamarthi, 2018;Otupiri et al, 2014;Vaik P et al, 2017;Verma et al, 2014), dan lingkar betis (Otupiri et al, 2014;Sheikh et al, 2017;Suneetha & Kavitha, 2016;Sunil Kumar, Sudarshan, & Vatsala, 2013) Pendeteksian BBLR secara cepat dan penanganan yang tepat merupakan hal yang penting terutama dalam kelangsungan hidup bayi (Administrative Committee on Coordination/ Subcommittee on Nutrition, 2000; Pojda & Kelley, 2000), namun sulit dilakukan jika persalinan terjadi di rumah dan tidak ditolong oleh non tenaga kesehatan yang disebabkan karena ketidaktersediaan alat penimbangan atau tidak adanya tenaga pengukur yang terlatih (Kusharisupeni et al, 2013;Neeluri & Pamarthi, 2018;Suneetha & Kavitha, 2016). Oleh karenanya diperlukan alternatif metode pendeteksian BBLR yang cepat, akurat dan mudah dilakukan.…”
Section: Pendahuluanunclassified
“…9,10 Epidemiological studies have shown that the children weighing less than 2.5 kilograms are nearly 20-times more likely to die than those who weigh 2.5 kilograms and more. 11 Other studies have stated that newborns with LBW were 5-10-times more likely to die than those who weighed 2.5 kilograms and more. 2,3 Prior studies have indicated that the newborn may develop macrosomia, defined as birth weight more than 4 kilograms.…”
Section: Introductionmentioning
confidence: 96%
“…A low-cost, easily accessible community measurement for LBW infants in areas where access to perinatal healthcare is reduced and neonatal mortality is high could aide in the detection of LBW infants and facilitate appropriate referral and support. Previous studies seeking to find a surrogate for LBW considered 4 anthropometric measurements, neonatal foot length ( 16–19 , 23 , 30–34 ), chest circumference ( 12–14 , 16 , 17 , 20 , 21 , 23 , 25 , 31 , 33 , 35 , 36 ), MUAC ( 12–14 , 16 , 21–25 , 33–37 ), and HC ( 13 , 17 , 20 , 22 , 25 ). However, the use of chest circumference and foot length measurements are not routine in most settings.…”
Section: Discussionmentioning
confidence: 99%